Management of Dystocia in Buffalo by Subcutaneous Fetotomy: A Case Report - Verma, A. K.; Kumar, R.; Jaiswal, S.; Verma, S. K.; Daund, S.; Kumar, R. (The Indian Journal of Animal Reproduction, 2021)
A 5 year old buffalo was presented at veterinary clinical complex for correction of  dystocia. The case was unsuccessfully handled by layman for the same. The visual  and vaginal examination revealed a dead fetus with both forelimbs protruded from  vulva and tightly impacted head with right lateral deviation. To resolve the case,  subcutaneous fetotomy was performed with judicious use of traction and followed  by a course of antibiotic, anti-inflammatory and antihistaminic to manage pain  and prevent secondary bacterial infection. The case was recovered uneventfully.  In conclusion, subcutaneous fetotomy can be used to resolve similar cases under  field conditions.
Keywords: Buffalo; Dystocia; Subcutaneous fetotomy; Head deviation